2021
DOI: 10.3390/oral1020007
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Nutritional Behavior and Oral Health Habits among Adults and Children in Nοrth-Eastern Greece

Abstract: The importance of the oral microbiota is strictly linked to global human health. When imbalance of the oral microbiota occurs, and it is characterized by shifts in bacterial composition and diversity; a state called dysbiosis is settled. There is an increasing amount of scientific evidence that this condition is associated with oral diseases caries, gingivitis and periodontitis. Diet seems to be a key factor for oral and dental health, impacting upon the oral microbiota. In an attempt to clarify the role of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“…For instance, in Thailand, children received health education every three months, showcasing the efficacy of such interventions [28]. Greek researchers compared different age groups and observed more pronounced benefits from educational interventions among the younger cohort [32]. Studies by Kariya et al [30], Lueangpiansamut et al [27], and da Silva et al [28] indicated that children with lower body mass index (BMI) faced an elevated risk of dental caries, although Rani et al [26] reported different findings in their survey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, in Thailand, children received health education every three months, showcasing the efficacy of such interventions [28]. Greek researchers compared different age groups and observed more pronounced benefits from educational interventions among the younger cohort [32]. Studies by Kariya et al [30], Lueangpiansamut et al [27], and da Silva et al [28] indicated that children with lower body mass index (BMI) faced an elevated risk of dental caries, although Rani et al [26] reported different findings in their survey.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Kariya et al [30], Lueangpiansamut et al [27], and da Silva et al [28] indicated that children with lower body mass index (BMI) faced an elevated risk of dental caries, although Rani et al [26] reported different findings in their survey. The evaluation of oral health was consistently conducted by experienced dentists across all studies [21,31,32], with oral health knowledge specifically assessed in only one study [23]. This study not only compared rural and urban populations but also juxtaposed their results with those from other counties [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their delicate balance can be easily disrupted by a variety of factors and, when this happens, it can lead to a variety of local diseases, such as cavities, gum disease, and halitosis, as well as some systemic diseases. Diet is an important factor affecting the oral microbiome, with the excess intake of processed foods, a common action in modern developed societies, being associated with a higher incidence of cavities and periodontal disease; the reduced intake of fruits and vegetables, causing less abundance of vitamins in the human host, also contributes to this scenario [ 3 , 4 ]. In this context, maintenance of adequate oral hygiene practices is essential to counteract the buildup of acid compounds resulting from sugar fermentation by the microbiome, avoid biofilm formation and reduce the risk of oral diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%